Pengaruh Paparan Warna Terhadap Retensi Short Term Memory Penderita Hipertensi Primer - Susanto, Rahmat (Jurusan Keperawatan FIKES UNSOED, 2012)
Hypertension patients are also potentially to damage brain function is anatomically and functionally. Many sufferers of hypertension as well as the long suffering from hypertension sufferer's quality of life including the influential on the quality of memory. The therapy has been used to prevent memory decline is with supplements consumption and also controls tight against the blood pressure with medication but untapped potential colors. The purpose of this research is to identify the influence of exposure to color (red, blue and green) on short term memory retention of hypertension sufferers. Design research is a Quasi Experimental Design and type design Only Non Equivalent Posttest Control Group Design. and the number of samples of 68 patients of hypertension according the criteria of inclusion. Results of this research show there is the influence of green color retention against short term memory with values p 0.001 and increase retention by 18.4% and results are not meaningful in red and blue colors with each p 0,243 and 0,831 by simply improving short term memory retention respectively at 2.3% and 0.1%. The department of health and hospitals use the color green room especially for painting the room on hypertension and the nurse to use the dominant color green on media outreach and health education.